2011
DOI: 10.1101/gr.116087.110
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic profiling of the human genome reveals gene products involved in plasma membrane targeting of SRC kinases

Abstract: SRC proteins are non-receptor tyrosine kinases that play key roles in regulating signal transduction by a diverse set of cell surface receptors. They contain N-terminal SH4 domains that are modified by fatty acylation and are functioning as membrane anchors. Acylated SH4 domains are both necessary and sufficient to mediate specific targeting of SRC kinases to the inner leaflet of plasma membranes. Intracellular transport of SRC kinases to the plasma membrane depends on microdomains into which SRC kinases parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…We also checked their role in previous screens using the same siRNAs or in other relevant studies (Dataset S3B). Interestingly, the largest group (33%) had been previously implicated in secretory trafficking (Simpson et al, 2012), followed by 23% in cell division (Neumann et al, 2010), 5% in plasma membrane targeting of Src kinases (Ritzerfeld et al, 2011), and 3% in a global set of CFTR interactors (Wang et al, 2006). Notably, in the latter group we found CFTR itself (plus APC, RYK, HSP90B1, COPB1).…”
Section: Resultsmentioning
confidence: 84%
“…We also checked their role in previous screens using the same siRNAs or in other relevant studies (Dataset S3B). Interestingly, the largest group (33%) had been previously implicated in secretory trafficking (Simpson et al, 2012), followed by 23% in cell division (Neumann et al, 2010), 5% in plasma membrane targeting of Src kinases (Ritzerfeld et al, 2011), and 3% in a global set of CFTR interactors (Wang et al, 2006). Notably, in the latter group we found CFTR itself (plus APC, RYK, HSP90B1, COPB1).…”
Section: Resultsmentioning
confidence: 84%
“…Notably, phosphorylation of N‐terminal serines by protein kinase C (PKC) isoforms enhances membrane interactions and biological activity of Lck (Yasuda et al ., ) as well as Nef (Wolf et al ., ). We recently identified PKCalpha as a critical component of PM delivery of the SH4 domains of the Leishmania protein HASPB and the SFK Yes (Ritzerfeld et al ., ), suggesting PKC‐mediated phosphorylation as a general regulatory mechanism of SH4 domain membrane interactions and intracellular transport. Moreover, SH4 domain trafficking appears to be regulated by dynamic phosphorylation/dephosphorylation cycles (Tournaviti et al ., ) and the outcome of this regulation may be SH4 domain specific as a function of, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While attempts to screen Leishmania genetically for effectors in this process have been challenging, a recent human genome-wide RNAi screen for factors involved in SH4-dependent protein targeting may be informative. Using SH4-HASPB–GFP and a mammalian SRC kinase YES-1 reporter (SH4-YES1-mCherry), 13 gene products were identified that may function primarily in HASPB targeting and a further 23 that are required for both HASPB and YES1 targeting ( Ritzerfeld et al ., 2011 ). Those with high scores in both HASPB and YES1 intracellular trafficking included COPB1 (a subunit of the coatomer complex), protein kinase C, the membrane receptors ITGAV (integrin alpha vitronectin) and ITGB1 (integrin beta 1), and PRP8 (pre-mRNA processing factor 8 homologue).…”
Section: Discussionmentioning
confidence: 99%